Leveraging Artificial Intelligence and Digital Technologies to Transform Learning and Mental Health Support: A Multidisciplinary Perspective for Educational Psychology (Proceeding International Collaborative Conference on Multidisciplinary Science, 2024)
The integration of artificial intelligence (AI) and digital technologies is revolutionising educational psychology, enhancing both personalised learning and mental health support. This narrative review explores these advancements through multidisciplinary perspectives, highlighting their impact on educational practices and student well-being. AI tools such as adaptive learning platforms and chatbots enable tailored educational interventions, improving engagement and academic outcomes. Similarly, digital mental health technologies, including therapy apps and telehealth services, provide scalable solutions for addressing psychological challenges. Despite their benefits, challenges such as algorithmic bias, data privacy concerns, and unequal access persist, particularly in low-resource settings. These issues highlight the need for ethical guidelines, infrastructural improvements, and culturally sensitive innovations. The review emphasises the critical role of multidisciplinary collaboration among educators, psychologists, and technologists to address these challenges effectively. Recommendations include developing culturally relevant tools, investing in educator training, and fostering interdisciplinary research. By leveraging AI and digital technologies responsibly, educational psychology can advance inclusive, equitable, and sustainable practices, enhancing both learning outcomes and mental health support for diverse student populations.